The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1183/09031936.00135312
|View full text |Cite
|
Sign up to set email alerts
|

Plasma advanced glycation end-products and skin autofluorescence are increased in COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with systemic inflammation and oxidative stress. These conditions may lead to the formation of advanced glycation end-products (AGEs).In this study we investigated in 88 COPD patients and 55 control subjects (80% ex-smokers) the association of the plasma protein-bound AGEs N e -(carboxymethyl)lysine (CML), pentosidine, N e -(carboxyethyl)lysine (CEL), and AGE accumulation in skin by skin autofluorescence (AFR), with lung function.Mean¡SD lysine and ex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 46 publications
5
47
1
Order By: Relevance
“…Fewer studies have demonstrated cross-sectional associations with biomarkers of oxidative stress. [18][19][20][21][22] Similar findings in populations with and without COPD suggest that the mechanisms responsible are not likely to be solely mediated by pulmonary inflammation, but may be related to other sources of systemic inflammation and oxidative stress. Chronic spinal cord injury (SCI) is characterized by abnormal pulmonary function as a consequence of respiratory system changes secondary to respiratory muscle weakness and paralysis, but is not known to result in pulmonary inflammation.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Fewer studies have demonstrated cross-sectional associations with biomarkers of oxidative stress. [18][19][20][21][22] Similar findings in populations with and without COPD suggest that the mechanisms responsible are not likely to be solely mediated by pulmonary inflammation, but may be related to other sources of systemic inflammation and oxidative stress. Chronic spinal cord injury (SCI) is characterized by abnormal pulmonary function as a consequence of respiratory system changes secondary to respiratory muscle weakness and paralysis, but is not known to result in pulmonary inflammation.…”
Section: Introductionsupporting
confidence: 50%
“…21 In 88 Dutch patients with moderate-to-severe COPD and 55 controls, the associations of percent-predicted FEV 1 with a number of measures of advanced glycation end-products were examined, with mixed results. In models adjusted for age, sex, person-years of smoking, BMI, HDL cholesterol, triglycerides, glomerular filtration rate, and CRP, N 6 -(carboxyethyl)lysine and skin autofluorescence were negatively associated and N 6 -(carboxymethyl)lysine was positively associated with percent-predicted FEV 1 , and the authors concluded that the exact role of these glycation end products remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…[a] isomerization, unknown ox. fragmentation various tissues, plasma, blood cells, urine, faecis, lens, reviewed in [89,90] N 6 -carboxyethyl lysine (CEL) [a] isomerization plasma [76,[91][92][93]; plasma, blood cells, urine [54,94]; lens [77,95] glycolic acid lysine amide (GALA) [b] isomerization lens [77] N 6 -formyl lysine [b] amine induced β-cleavage plasma [76], lens [77] N 6 -acetyl lysine [b] amine induced β-cleavage plasma [76], lens [77] N 6 -oxalyl lysine [b] ox. α-cleavage, amine induced β-cleavage lens [77] N 6 -lactoyl lysine [b] amine induced β-cleavage plasma [76]; lens [77] N 6 -glycerinyl lysine [b] amine induced β-cleavage plasma [76] N 6 -threonyl lysine [b] ox.…”
Section: Discussionmentioning
confidence: 99%
“…This was in reasonable agreement with data described in literature [36][37][38][39][40][41] . The described method is suitable for studying AGEs in several different human and animal studies [42][43][44][45][46][47][48][49] and is a strong tool to investigate the putative effects of AGEs in the pathophysiology of different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of glucose to sorbitol and further oxidation to fructose and fructose-3-phosphate leads to the formation of 3-DG. Thus, AGEs can be formed by these sugar-derived carbonyls 45 , by lipid peroxidation and oxidative stress 46,47 or by reactions between pentoses and proteins, known as the fluorescent lysine-arginine cross-link pentosidine 36,48 .…”
mentioning
confidence: 99%